2019
DOI: 10.1371/journal.pone.0217983
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent event survival analysis predicts future risk of hospitalization in patients with paroxysmal and persistent atrial fibrillation

Abstract: Background In patients with paroxysmal atrial fibrillation (PAF) or persistent atrial fibrillation (PeAF) symptom burden and fear of hospital readmission are major causes of reduced quality of life. We attempted to develop a prediction model for future atrial fibrillation hospitalization (AFH) risk in PAF and PeAF patients including all previously experienced AFHs in the analysis, as opposed to time to first event. Methods Recurrent event survival analysis was used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Regarding hospitalizations, a recent small study suggested that persistent AF be associated with higher future AF-hospitalizations. 22 We consider our findings important from an epidemiological perspective, given the association of multiple hospitalizations with an impaired quality of life and an increased financial burden worldwide. 7,[23][24][25] No significant differences in stroke incidence were detected among all AF patterns.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding hospitalizations, a recent small study suggested that persistent AF be associated with higher future AF-hospitalizations. 22 We consider our findings important from an epidemiological perspective, given the association of multiple hospitalizations with an impaired quality of life and an increased financial burden worldwide. 7,[23][24][25] No significant differences in stroke incidence were detected among all AF patterns.…”
Section: Discussionmentioning
confidence: 93%
“…In practice, this means that having already experienced one or more recurrent events may or may not influence the risk of further occurrences. This is a remarkable feature of the confidence interval formula because in practice, patients that have already experienced an event are often more likely to experience future occurrences (22).…”
Section: Toolbox 2: Right Censoringmentioning
confidence: 99%
“…Such recurrent events are often highly associated with patients' disease progression and survival. [1][2][3][4] There is significant interest in comprehending the relationship between recurrent events and terminal events. [5][6][7][8][9] Specifically, there is an urgent need for appropriate methods to thoroughly examine the role of these recurrent events in the causal pathway between exposure to time-to-event outcomes, such as death, failure, relapse, or the emergence of a new illness.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include repeated asthma attacks, recurrent hospitalizations, recurrence of leukemia and other cancers, as well as multiple opportunistic infections (OIs) in Human Immunodeficiency Virus (HIV)‐infected patients. Such recurrent events are often highly associated with patients' disease progression and survival 1‐4 . There is significant interest in comprehending the relationship between recurrent events and terminal events 5‐9 .…”
Section: Introductionmentioning
confidence: 99%